Massive splenomegaly in scrub typhus: A rare presentation. (2020) - Atam, Virendra; Majumdar, Avirup; Himanshu, D.; Kumar, Vivek; Atam, Isha
Highlights: Scrub Typhus is an emerging potential cause of Pyrexia of Unknown Origin (PUO), specially in Tropical countries like India The disease can have a wide spectrum of symptomatology, ranging from mild self limiting disease to fatal multiorgan failure Massive splenomegaly, although extremely rare, can be due to Scrub Typhus Possibility of Scrub Typhus should always be kept in mind in cases of non resolving fever presenting with splenomegaly Abstract: Scrub typhus, an acute rickettsial febrile illness, is an emerging cause of prolonged fever and Pyrexia of Unknown Origin(PUO). Scrub typhus infection can have myriads of clinical manifestations ranging from mild asymptomatic disease to fatal multi-organ failure. Massive splenomegaly in scrub typhus is rarely reported. We present a diagnostic conundrum of a 22 year old male presenting with fever, hepatomegaly, massive splenomegaly and lymphadenopathy. Tests for malarial parasite, visceral leishmaniasis, enteric fever were negative. Bone marrow aspiration showed normal hemopoeisis. IgM Scrub tested positive. High grade of clinical suspicion and awareness is required among treating physicians for early diagnosis of scrub since delay in treatment initiation may lead to a dismal clinical outcome.